Financial Feasibility Analysis of Layer Chicken Farming at PT Mitra Sejati, Konawe Selatan Regency - Ayu Warni Erika Priski; Hajar Hajar; Awal Maulid Sari (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
This study aimed to analyze the production cost structure, revenue, income, and financial feasibility of the commercial laying hen enterprise operated by PT Mitra Sejati in Konda District, South Konawe Regency, Southeast Sulawesi Province. The research was conducted from July to August 2025 using a quantitative descriptive approach. Data were collected through direct observation, interviews with the owner and employees, documentation of production records, and analysis of supporting secondary data. The variables analyzed included farm profile, production resources, investment costs, production costs, revenue, income, and financial feasibility using income analysis, Revenue–Cost Ratio (R/C Ratio), and Benefit–Cost Ratio (B/C Ratio). The results showed that PT Mitra Sejati experienced significant business development, increasing from 3,000 laying hens in 2023 to 8,000 birds in 2025, with 4,200 productive hens producing approximately 140 trays of eggs per day. The total investment cost reached IDR 254,800,000, while total production costs during one 18-month production cycle amounted to IDR 3,736,020,857. Total revenue obtained from egg sales, culled hens, and poultry manure reached IDR 3,979,400,000, resulting in a net income of IDR 243,379,143 or an average monthly income of IDR 13,521,064. The financial feasibility analysis indicated an R/C Ratio value of 1.07 and a B/C Ratio value of 0.07, demonstrating that the enterprise was economically feasible and generated positive returns. However, feed costs represented the largest production expenditure, accounting for approximately 70% of total costs, indicating that feed efficiency improvement remains a major strategy for increasing profitability. Overall, PT Mitra Sejati’s commercial laying hen enterprise has good development prospects, supported by effective production management, diversified revenue sources, and continuous improvement in operational efficiency.